Financial Market Integration and World Economic Stabilization toward Purchasing Power Parity - Tatsuyoshi Okimoto; Katsumi Shimotsu (Queen's University, Department of Economics, 2007)
Purchasing power parity (PPP) is one of the most important, but empirically controversial theories in international macroeconomics. Although many researchers believe that some variant of PPP holds in the long run, there are diverse empirical results regarding the PPP hypothesis. We examine the PPP hypothesis from an alternate point of view: We investigate the possibility of financial market integration, and world economic stabilization toward PPP, by examining the change in the persistence of PPP deviations during the last three decades. We employ a fractional integration framework, which provides a powerful tool to detect changes in the persistence for highly persistent time series. First, we test the null hypothesis of no decline in the persistence of PPP deviations. The test rejects the null at the 10% significance level for 11 out of 17 countries, thus providing strong support for financial market integration and world economic stabilization toward PPP. Second, we examine the dynamics of the persistence of PPP deviations during the last three decades through rolling-window estimation. Our results show that the persistence of PPP deviations has decreased gradually, and that many real exchange rates have experienced a sharp drop in their persistence once samples starting in the mid-1980s are used. Interestingly, this timing almost coincides with the timing of U.S./world economic stabilization reported by other studies. We also examine the relation between the persistence of PPP deviations and de facto measures of financial integration by Lane and Milesi-Ferretti (2006). We confirm that they are strongly correlated for all countries. This finding suggests that the recent promotion of financial integration is one of the main sources of the decline in the persistence of PPP deviations.
Keywords: C14; C22; F31; F36; 330; fractional integration; PPP; real exchange rate; financial integration; Internationaler Finanzmarkt; Integration; Kaufkraftparität; Internationale Konjunktur; Theorie